New Insights Into Vertigo Attack Frequency as a Predictor of Ischemic Stroke - Qiu, Dongxu; Zhang, Lei; Deng, Jun; Xia, Zhiwei; Duan, Jingfeng; Wang, Juan; Zhang, Rongsen (Frontiers in Neurology, 2020)
Background: Recurrent vertigo attack account for 2.6 million US emergency department visits per year, more than 4% attributable to ischemic infarction. However, few studies were performed to investigate the frequency characters of vertigo attack prior the ischemic stroke. Methods: To address this issue, we conducted this retrospective analysis and manually screened the medical records of 231 patients who experienced the recurrent vertigo attack prior ischemic stroke. Patients were divided into 4 different groups based on vertigo attack frequency as well as the ischemic infarction territory. Vertigo attack ≤2 times preceding the ischemic stroke was defined as the low frequency group. Vertigo attack ≥3 times was defined as the high frequency group. Clinical parameters, including the vascular risk factors, the average NIHSS score and the infarction volume, were evaluated between the group. Results: By comparing the vascular risk factors between low and high frequency group, we indicated that patients in posterior infarction of high frequency group exhibited a higher prevalence of vertebral artery stenosis. Yet, the incidence of diabetic mellitus was increased in low frequency group. In addition, patients in posterior infarction of low frequency group tended to be more actively seeking the medical intervention after the vertigo arise. Notably, the brain stem, especially the lateral medullary, had higher probability to be inflicted in posterior infarction of high frequency group. Whereas, the cerebellum was more commonly involved in posterior infarction of low frequency group. Conclusions: Our findings indicated that the clinical parameters, including the artery stenosis, diabetic mellitus and the MRI image findings, were different between low and high frequency group. We also found that patients from high frequency group were more willing to seek for the medical intervention after the vertigo symptom arise. Those findings could be valuable for the clinician to choose the specific examination for patients according to their frequency of vertigo attack.